Preparation of micron–sized polystyrene/silver core–shell microspheres by ultrasonic assisted electroless plating. (20th January 2021) - Cheng, Junhua; Gan, Guoyou; Li, Junpeng; Yu, Xianglei; Tang, Lin; Liu, Chengbin
Abstract: In the study, PS/Ag composite microspheres with polystyrene (PS) core and silver shell were synthesized by ultrasonic electroless plating. The samples were characterized by SEM, FTIR and XRD. The effects of times of sensitization and silver plating, mass ratio of AgNO3 to PS microspheres and stirring method on the preparation and dispersion of PS/Ag microspheres were studied. The results show that the more times of sensitization and silver plating, the more uniform the silver deposition on the surface of microspheres. When the mass ratio of AgNO3 to PS microspheres is 2: 1, it can promote the uniform coating of silver shell and reduce the content of free silver. Ultrasonic assisted electroless plating for 10 min can prevent PS/Ag microspheres from agglomerating and improve the speed of electroless plating. The thickness of the silver shell on the surface of the PS microsphere is about 200 nm.